2017
DOI: 10.1186/s12993-017-0120-9
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ pupillary responses to infant facial expressions

Abstract: BackgroundHuman parental care relies heavily on the ability to monitor and respond to a child’s affective states. The current study examined pupil diameter as a potential physiological index of mothers’ affective response to infant facial expressions.MethodsPupillary time-series were measured from 86 mothers of young infants in response to an array of photographic infant faces falling into four emotive categories based on valence (positive vs. negative) and arousal (mild vs. strong).ResultsPupil dilation was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…For instance, pupillary dilatation reflects preference for political candidates (Barlow, 1969), alcoholic beverages (Beall, 1977) and visual arts (e.g., Rembrandt’s paintings) (Elschner, Hübner & Dambacher, 2017; Hayes, Muday & Schirillo, 2013; Kuchinke et al., 2009; Powell & Schirillo, 2011; Schirillo, 2014; Alvarez et al., 2015) allowing to predict people’s tastes. Images of human faces elicit a pupillary reaction as well: Angry or fearful facial expressions and images of females increase pupil sizes, in contrast to happy faces and males’ images (Allard, Wadlinger & Isaacowitz, 2010; Blackburn & Schirillo, 2012; Bradley et al., 2008; Chiesa et al., 2015; Goldinger, He & Papesh, 2009; Kret et al., 2013; Lichtenstein-Vidne et al., 2017; Porter, Hood & Troscianko, 2006; Schrammel et al., 2009; Vanderhasselt et al., 2018; Wu, Laeng & Magnussen, 2012; Yrttiaho et al., 2017; Kret, 2017; Hammerschmidt et al., 2018). Negative images showing violence, distress and threat but also positive ones depicting happiness elicited a dilatation as opposed to neutral everyday images (Henderson, Bradley & Lang, 2014; Bradley, Sapigao & Lang, 2017; Henderson, Bradley & Lang, 2017; Iijima et al., 2014; Chiew & Braver, 2014; Pearlstein et al., 2018; Thoma & Baum, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, pupillary dilatation reflects preference for political candidates (Barlow, 1969), alcoholic beverages (Beall, 1977) and visual arts (e.g., Rembrandt’s paintings) (Elschner, Hübner & Dambacher, 2017; Hayes, Muday & Schirillo, 2013; Kuchinke et al., 2009; Powell & Schirillo, 2011; Schirillo, 2014; Alvarez et al., 2015) allowing to predict people’s tastes. Images of human faces elicit a pupillary reaction as well: Angry or fearful facial expressions and images of females increase pupil sizes, in contrast to happy faces and males’ images (Allard, Wadlinger & Isaacowitz, 2010; Blackburn & Schirillo, 2012; Bradley et al., 2008; Chiesa et al., 2015; Goldinger, He & Papesh, 2009; Kret et al., 2013; Lichtenstein-Vidne et al., 2017; Porter, Hood & Troscianko, 2006; Schrammel et al., 2009; Vanderhasselt et al., 2018; Wu, Laeng & Magnussen, 2012; Yrttiaho et al., 2017; Kret, 2017; Hammerschmidt et al., 2018). Negative images showing violence, distress and threat but also positive ones depicting happiness elicited a dilatation as opposed to neutral everyday images (Henderson, Bradley & Lang, 2014; Bradley, Sapigao & Lang, 2017; Henderson, Bradley & Lang, 2017; Iijima et al., 2014; Chiew & Braver, 2014; Pearlstein et al., 2018; Thoma & Baum, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study with young children (3–5 years old) showed that the previously described attentional bias for angry faces is stronger when pictures of child (vs. adults) models are used [24]. Another important line of research did not focus on children’s responses, but rather on the behavioral [25,26] or psychophysiological responses of adults in general, or parents [2729], to children’s emotional expressions. For example, Aradhye et al [4] used photographs of children to examine how different expressions influence the responsiveness of non-kin young adults and found that smiling children were rated as more likely to be adopted than crying children.…”
Section: Introductionmentioning
confidence: 99%
“…Rembrandt's paintings) [121][122][123][124][125][126] allowing to predict people's tastes. Images of human faces elicit a pupillary reaction as well: Angry or fearful facial expressions and images of females increase pupil sizes, in contrast to happy faces and males' images [127][128][129][130][131][132][133][134][135][136][137][138][139][140] . Negative images showing violence, distress and threat but also positive ones depicting happiness elicited a dilatation as opposed to neutral everyday images 141 142-147 .…”
Section: Pupillary Dilatation: Cognitionmentioning
confidence: 99%